2012
DOI: 10.1167/iovs.12-9457
|View full text |Cite
|
Sign up to set email alerts
|

MMP2 Activity is Critical for TGFβ2-Induced Matrix Contraction—Implications for Fibrosis

Abstract: PURPOSE. The fibrotic lens disorder posterior capsule opacification (PCO) develops in millions of patients following cataract surgery. PCO characteristics are extensive extracellular matrix (ECM) production and contraction of the posterior lens capsule, resulting in light-scattering ECM modification (wrinkling). The pro-fibrotic cytokine transforming growth factor beta (TGFb) is central to PCO development. This study aimed to elucidate the role of the ECM modulators matrix metalloproteinases (MMPs) in TGFb-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…This is comparable to studies on human capsular bag models that have also revealed up-regulation of MMPs 2 and 9 following exposure to TGFb2 and the presence of MMP2 in ex vivo tissue from PCO patients (Wormstone et al, 2002b), and inhibition of MMP2 in prevention of TGFb2-induced capsular wrinkling (Eldred et al, 2012). In contrast, research by Lee et al (2002) have shown that rather than promoting cell proliferation TGFb induces apoptotic cell death of HLEB3 cells by decreasing BCL2 levels (Lee et al, 2002).…”
Section: Cell Linessupporting
confidence: 76%
See 2 more Smart Citations
“…This is comparable to studies on human capsular bag models that have also revealed up-regulation of MMPs 2 and 9 following exposure to TGFb2 and the presence of MMP2 in ex vivo tissue from PCO patients (Wormstone et al, 2002b), and inhibition of MMP2 in prevention of TGFb2-induced capsular wrinkling (Eldred et al, 2012). In contrast, research by Lee et al (2002) have shown that rather than promoting cell proliferation TGFb induces apoptotic cell death of HLEB3 cells by decreasing BCL2 levels (Lee et al, 2002).…”
Section: Cell Linessupporting
confidence: 76%
“…maintain transdifferentiation and promote matrix contraction (Wormstone et al, 2006a). Furthermore, MMP2 inhibition was found to play an important role in TGFb induced changes within the capsular bag (Eldred et al, 2012).…”
Section: Capsular Bagsmentioning
confidence: 97%
See 1 more Smart Citation
“…Because the cataract is disease of old age, embryonic cells will not completely mimic clinical situations. However, while primary lens cell cultures from aged human donors are useful, human LECs transformed virally 1,44 or non-virally 45 have been used to study the mechanisms involved in the pathogenesis of PCO. In addition, LECs derived from animals, including weanling mice 46 and chicken embryos, 47 have also been used for PCO analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs because the trauma of surgery can induce expression of many TGF-β activators, such as plasmins, cathepsins, MMPs [34] and thrombospondin-1 [35] which cleave latent TGF-β precursor protein. Furthermore, TGF-β itself is capable of increasing expression of MMPs, including MMP2 which could further accelerate conversion of latent TGF-β to its active form [16,36,37]. In addition, elevated numbers of reactive oxygen species are also reported to promote TGF-β activity [38,39].…”
Section: Growth Factorsmentioning
confidence: 99%